The Impact of Benevolent Sexism on Women’s Career Growth: A Moderated Serial Mediation Model - Shuang Song; Po-Chien Chang (Behavioral Sciences)
This study investigates how benevolent sexism impedes women’s career growth, focusing on the mediating roles of self-esteem and emotional exhaustion and the moderating role of career development strategies. Using a three-wave, time-lagged survey, data from 410 female employees across various industries in China were analyzed with SPSS 24.0 and Mplus 8.3. Results indicate that benevolent sexism negatively influences career growth via reduced self-esteem and increased emotional exhaustion. Moreover, career development strategies mitigate this adverse effect, weakening the relationship between benevolent sexism and career growth. Higher levels of career development strategies lessen the detrimental impact of benevolent sexism on women’s professional progress. These findings enrich Cognitive-Affective Personality System theory by clarifying the mechanisms through which benevolent sexism undermines career development. They also highlight the practical significance of adopting robust career strategies to promote workplace gender equality and offer empirical insights into the broader implications of benevolent sexism on women’s career advancement.